Gregory of Nyssa : the letters - Gregory, of Nyssa, Saint, approximately 335-approximately 394 (Supplements to Vigiliae Christianae ;, 2007)
This book gathers 37 letters of St Gregory of Nyssa (c. 335-394), translated into English, some for the first time, and equipped with up-to-date scholarly notes. It begins with a biography focusing on Gregory's family background and young adulthood. A study of Gregory the letter writer follows, with a dateline of the letters. Three sub-collections of letters follow: 1. 'Prelude' comprising testimonia from Basil and Gregory Nazianzen, 2. 'The Pasquali Collection', the 30 letters established by G. Pasquali, 3. 'Supplementary', one letter always known as Gregory's, five letters reassigned to Gregory by scholars, and a new one proposed by the author for reassignment. A specially commissioned icon, an original map, and two architectural sketches are included. This book will both stimulate veteran scholars in the Cappadocian Fathers and early Christianity, and serve English speaking lovers of the Fathers who do not have ready access to the sources in other languages.